Assessment of risk factors for Neonatal Abstinence Syndrome (NAS) using a Standardized Surveillance Case Definition in Clark County, NV - Bryant, Rachel; Delise, Brandon; Zhang, Ying; Beckford, Niema; Lockett, Cassius (Journal of Maternal and Child Health, 2024)
Background: Neonatal Abstinence Syndrome (NAS) is a withdrawal syndrome in neonates that can occur due to drug exposure during pregnancy. This study had two objectives: (1) Assess the implementation of the Council of State and Territorial Epidemiologists (CSTE) Tier 2 case definition for NAS surveillance in Clark County, Nevada and (2) Identify risk factors for NAS. Subjects and Method: This study utilized hospital discharge data. Claim-based records from non-federal acute care hospitals located in Clark County during 2016-2022 were analyzed.  All newborn inpatient discharge records from January 1, 2016 to September 30, 2022 in Clark County, Nevada were selected.  ICD-10-CM codes were utilized based on the CSTE Tier 2 case definition. Any neonate record that met the case definition, including any record with the diagnosis code P96.1, was considered a NAS confirmed case. Codes for suspect cases, maternal history of substance use, unspecified maternal medication, and transmitted noxious-substances were also assessed. A multiple logistic regression model using backward stepwise selection was developed to find risk factors related to NAS-confirmed births. Results: In Clark County, Nevada, the NAS incidence rate from January 2016 to September 2022 was 7.4 per 1,000 births. In 2022 alone, the rate of NAS was 8.9 per 1,000 births. Estimated rates of NAS were highest among neonates who were White at 13 per 1,000 births. Hospital J, the largest academic medical center in Southern Nevada, had the highest NAS confirmed case rate at 11.3 per 1000 newborn hospitalizations. Results from the multiple logistic regression model showed the odds of being born with NAS among neonates who identified as White were 5.0 (OR=5.17; 95% CI= 4.29 to 6.24; p <0.001) times more likely to have NAS compared to the Hispanic group. Conclusion: Given that 2022 had the highest rate of confirmed NAS cases there is a need to collect substance and diagnosis-specific data about prenatal substance use to identify unmet service care and disparities.